ЯНГИ ЎЗБЕКИСТОНДА БАРКАМОЛ АВЛОДНИ СПОРТГА ТАЙЁРЛАШНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ - Мырзамбетов, П.Ш. (SCIENCE and SOCIETY, 2023)
This article examines the level of physical breakdown in the human body, determining not only the physiological capabilities of a person, but also the spiritual quality of a person; physical training of an athlete, physical training, education, strength of endurance and sliding. The structure of psychological training of a high rank differs from the chosen kind of sport by the number and character of the picture, which is unique for these sports. One of the key aspects of spiritual training is the ability to predict future trends. The definition of a prophecy depends on the athlete's experience of his / her competitor, his / her full potential assessment. Experienced Trainer - A trainer who believes that the ability to predict competitions is one of the key players in high teaching skills that they can combine with their technical and tactical physical and psychological preparation.
Keywords: scientific - stylistic and psychological pedagogic basis of appealing youngster’s attention to sport; forms; conditions; peculiarities physical qualities; physical preparations; mendal preparations; sports competitions; factors; predicting